Natural colorants improved the physicochemical and sensorial properties of frozen Brazilian sausage (linguica) with reduced nitrite - Bonadio Bellucci, Elisa Rafaela [UNESP]; Barretto, Tiago Luis; Lorenzo Rodriguez, Jose Manuel; Bis-Souza, Camila Vespucio [UNESP]; Barba, Francisco Jose; Silva Barretto, Ndrea Carla da [UNESP] (Univ Sao Paolo, 2021)
The use of natural colorants in meat products can keep its coloring attractive as well as meet the demand from consumers interested in products that are healthier. Nitrite is added as a preservative to these products and it is also a precursor of the generation of a specifically desired color in meat products. However, its use has been associated with the development of certain kinds of cancer. The objective of this study was to evaluate the effect of reduced levels of nitrite in Brazilian sausage (linguica) with natural colorants on the physicochemical and sensorial properties following frozen storage. Nine treatments were tested: 0.015 % nitrite (C150), 0.0075 % nitrite (C75) and 0 % nitrite (C0), 0.0075 % nitrite and 1.5 % microencapsulated betalain (BME75), 0 % nitrite and 1.5 % microencapsulated betalain (BME0), 0.0075 % nitrite and 0.19 % commercial betalain (BCP75), 0 % nitrite and 0.19 % commercial betalain (BCP0), 0.0075 % nitrite and 0.02 % of cochineal carmine (CC75) and 0 % nitrite and 0.02 % of cochineal carmine (CC0). Oxidative stability, residual nitrite and instrumental color were the determinant factors. Sensory analysis was directed at color, texture, taste and global acceptance. Natural colorants did not have any antioxidant effect. Sausages prepared with betalain and 0.0075 % nitrite showed the highest a* values. The addition of colorants improved both color and overall acceptance. The addition of betalain and cochineal carmine with 0.0075 % nitrite proved to be effective in achieving high acceptability in Brazilian sausage (linguica).
Keywords: betalain; sensory evaluation; cochineal carmine; lipid oxidation